Amorphous Core–Shell Nanoparticles as a Highly Effective and Stable Battery‐Type Electrode for Hybrid Supercapacitors. Issue 19 (12th August 2019) - Cheng, Danyu; Zhong, Qin; Wang, Juan; Bu, Yunfei
Abstract: Herein, a silver@amorphous nickel–cobalt hydroxide (Ag@NCOH) battery‐type electrode with the morphology of core–shell nanoparticle is successfully fabricated through coordination etching and precipitating route. This electrode exhibits excellent electrochemical performance, including superior specific capacity (≈718.1 C g −1 at 1 A g −1 ), excellent rate capability (71.9% capacity retention at 30 A g −1 ), as well as good cycling stability (83.2% capacity retention over 4000 cycles) for hybrid supercapacitors. According to the results of the characterization analysis and systematic electrochemical testing, the Ag nanoparticles in core–shell structure can significantly enhance the conductivity and accelerate the rate of electron transport. Meanwhile, the nanostructures and grain boundaries of amorphous hydroxide materials can effectively improve to expose the electrochemical active sites to electrolyte. Moreover, the hybrid supercapacitor assembled from Ag@NCOH and active carbon (AC) exhibits good performance (energy density of 39.88 W h kg −1 at power density of 375 W kg −1 ) and superior cycling stability (85.39% capacitance retention over 9000 cycles). This work demonstrates an effective strategy to construct highly effective and stable amorphous electrode materials for hybrid supercapacitors. Abstract : An amorphous nanoparticles electrode (a battery‐type electrode) with silver@amorphous nickel–cobalt hydroxide core–shell nanoparticle structure is synthesized via coordination etching and precipitating route. Benefiting from amorphous core–shell nanostructure and elemental composition of electrode materials, the Ag@NCOH electrode demonstrates highly effective and stable electrochemical performance for hybrid supercapacitors.